2015
DOI: 10.1104/pp.15.00478
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Movement of Cellulose Synthase Complexes in Arabidopsis Seed Coat Epidermal Cells Deposit Cellulose Involved in Mucilage Extrusion, Adherence, and Ray Formation

Abstract: CELLULOSE SYNTHASE5 (CESA5) synthesizes cellulose necessary for seed mucilage adherence to seed coat epidermal cells of Arabidopsis (Arabidopsis thaliana). The involvement of additional CESA proteins in this process and details concerning the manner in which cellulose is deposited in the mucilage pocket are unknown. Here, we show that both CESA3 and CESA10 are highly expressed in this cell type at the time of mucilage synthesis and localize to the plasma membrane adjacent to the mucilage pocket. The isoxaben r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
101
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(104 citation statements)
references
References 96 publications
3
101
0
Order By: Relevance
“…5; Supplemental Fig. S4; Harpaz-Saad et al, 2011;Mendu et al, 2011;Sullivan et al, 2011;Griffiths et al, 2014Griffiths et al, , 2015. We propose that a GGM scaffold surrounds the cellulosic rays in the mucilage capsule (Fig.…”
Section: Ggm Scaffolds and Cellulosic Rays Maintain The Architecture mentioning
confidence: 99%
See 1 more Smart Citation
“…5; Supplemental Fig. S4; Harpaz-Saad et al, 2011;Mendu et al, 2011;Sullivan et al, 2011;Griffiths et al, 2014Griffiths et al, , 2015. We propose that a GGM scaffold surrounds the cellulosic rays in the mucilage capsule (Fig.…”
Section: Ggm Scaffolds and Cellulosic Rays Maintain The Architecture mentioning
confidence: 99%
“…The structure of homogalacturonan (HG), the major pectin in primary cell walls but a minor mucilage component, appears to be a key determinant of gelling properties and mucilage extrusion (Rautengarten et al, 2008;Saez-Aguayo et al, 2013;Voiniciuc et al, 2013). Mucilage attachment to seeds is maintained by the SALT OVERLY SENSITIVE5 glycoprotein and cellulose synthesized by multiple CELLULOSE SYNTHASE (CESA) isoforms (Harpaz-Saad et al, 2011;Mendu et al, 2011;Sullivan et al, 2011;Griffiths et al, 2014Griffiths et al, , 2015. From more than 35 genes that are reported to affect Arabidopsis seed mucilage properties , only CSLA2, CESA3, CESA5, GALACTURONOSYLTRANSFERASE11 (GAUT11; Caffall et al, 2009), and GAUT-LIKE5 (GATL5; Kong et al, 2013) are predicted to encode GTs.…”
mentioning
confidence: 99%
“…Mucilage mutants also have been identified that are affected in enzymes implicated in polysaccharide synthesis: mucilage modified4 (mum4)/rhamnose biosynthetic gene2 (rhm2), galacturonosyltransferase-like5 (gatl5), and galacturonosyltransferase11 (gaut11) have reductions in mucilage Rha and/or GalA contents (Usadel et al, 2004;Western et al, 2004;Oka et al, 2007;Caffall et al, 2009;Kong et al, 2013), whereas cellulose production is reduced in the inner mucilage layer of cellulose synthase5 (cesa5)/mum3, the cesa3 mutant irregular xylem1-1 (irx1-1), and fei2 (Harpaz-Saad et al, 2011;Mendu et al, 2011;Sullivan et al, 2011;Griffiths et al, 2015). Although the total amount of mucilage pectin is unchanged in the latter mutants, their partitioning is modified in cesa5 and fei2, with a reduction observed in the inner layer demonstrating that cellulose plays a crucial role in anchoring mucilage pectin to the seed coat surface.…”
mentioning
confidence: 99%
“…In Arabidopsis, the CESA gene family has 10 members (Richmond, 2000): CESA1, CESA3, CESA6, and CESA6-like (CESA2, CESA5, and CESA9) are involved in primary cell wall biosynthesis (Arioli et al, 1998;Fagard et al, 2000;Scheible et al, 2001), CESA4, CESA7, and CESA8 are involved in secondary cell wall biosynthesis (Turner and Somerville, 1997;Taylor et al, 1999Taylor et al, , 2003, and CESA10 appears to function in the production of seed coat mucilage (Griffiths et al, 2015). Specifically for primary wall CSCs, biochemical and genetic studies have indicated that CESA1 and CESA3 are constitutive components of the CSC, whereas CESA6 and CESA6-like proteins have partially redundant functions and likely constitute a third catalytic component of the CSC (Desprez et al, 2007;Persson et al, 2007).…”
mentioning
confidence: 99%